Muonium Chemistry at Diiron Subsite Analogues of [FeFe]‐Hydrogenase. (14th October 2016) - Wright, Joseph A.; Peck, Jamie N. T.; Cottrell, Stephen P.; Jablonskytė, Aušra; Oganesyan, Vasily S.; Pickett, Christopher J.; Jayasooriya, Upali A.
Abstract: The chemistry of metal hydrides is implicated in a range of catalytic processes at metal centers. Gaining insight into the formation of such sites by protonation and/or electronation is therefore of significant value in fully exploiting the potential of such systems. Here, we show that the muonium radical (Mu . ), used as a low isotopic mass analogue of hydrogen, can be exploited to probe the early stages of hydride formation at metal centers. Mu . undergoes the same chemical reactions as H . and can be directly observed due to its short lifetime (in the microseconds) and unique breakdown signature. By implanting Mu . into three models of the [FeFe]‐hydrogenase active site we have been able to detect key muoniated intermediates of direct relevance to the hydride chemistry of these systems.